The Importance Of Grammar Learning Strategies - Saidova Maʼmura Sulaymonovna (European Journal of Life Safety and Stability (2660-9630), 2022)
Although major advances have been made in research on language learning strategies (LLS), there are some areas that have been somewhat surprisingly neglected by specialists. This applies without doubt to the strategies that learners draw on to better understand and learn grammar rules but also to employ grammar structures in real-time processing, as required in spontaneous communication.